Strategic analysis of the company Urdiamant, Ltd. - Matús, Eduard (2013)
This thesis focuses on the topic of forming business strategies. In the theoretical part are summarized methodologies and tools that can be employed for evaluating and crafting competitive strategies in an environment where the only constant variable is change. The author discusses various approaches towards the strategy creation process, bearing the prescriptive school of thought as a cornerstone ideology. Goal of this thesis is to employ the acquired knowledge on a practical example of the company Urdiamant, s.r.o. One of this company's divisions serves as a subject for analysis and development of a feasible business strategy that would help the division in achieving a competitive advantage and creating an organizational structure and culture, which will enable adaptation to today's ever-changing environment without loosing the advantageous state.